ICCPR and the Future of Political Rights: A Critical Analysis of Existing International Legal Norms - Farisi, Mochammad; Ardiana, Hanny Sukma; Bahren, Bahren; Harahap, Rahayu Repindowaty (Uti Possidetis: Journal of International Law, 2025)
Background: This article examines the normative gap within the International Covenant on Civil and Political Rights (ICCPR) concerning the regulation of internal democracy within political parties. While Article 25 guarantees the procedural right to vote and to be elected, it does not sufficiently address substantive democratic deficits such as oligarchic practices, vote buying, and the absence of internal party accountability. Methodology: The analysis is grounded in normative legal research, relying on doctrinal interpretation of international human rights instruments, particularly the ICCPR, and exploring the horizontal application of human rights and the state's due diligence obligations with respect to political parties. Objectives: The primary objective is to argue that political parties, as pivotal actors in democratic systems, should be subject to human rights standards, especially regarding integrity, participation, and non-discrimination, and to identify legal mechanisms that could strengthen internal party democracy under international law. Findings: The study finds that existing international legal instruments inadequately regulate the internal functioning of political parties, allowing undemocratic practices that undermine the substantive realization of political rights. It also identifies that the state's positive obligations can justify regulatory oversight of political party governance. Originality/Novelty: This article advances three normative proposals to fill the regulatory void: the drafting of a new General Comment to Article 25 of the ICCPR, the adoption of an Optional Protocol to impose binding obligations, and the creation of UN Guiding Principles as soft law. These proposals collectively offer a novel framework for reconstructing political rights substantively and reinforcing democratic legitimacy through international law.